Nilai tambah dan preferensi konsumen terhadap produk olahan beras (Studi kasus usaha rengginang Original di Desa Kasumewuho Kecamatan Wawotobi Kabupaten Konawe) - Yuniar, Anna; Gafaruddin, Abdul; Zani, Munirwan (Jurnal Sosio Agribisnis, 2023)
The abundant amount of rice production in Konawe Regency is an opportunity for the community, especially MSME entrepreneurs, to earn more income by increasing the added value of processing rice into rengginang products. Consumer decisions in buying rengginang will provide opportunities for producers to provide products that suit consumer preferences. The purpose of this study is to determine the added value obtained in the rengginang production business, as well as to determine consumer preferences for the most considered attributes of rengginang products in Kasumewuho Village, Wawotobi District, Konawe Regency. The study was conducted from November 2022 to March 2023. The number of respondents was 1 producer by conducting case studies and determining consumer samples using accidental sampling with a minimum sample method that produced a sample of 40 consumers. Data collected for added value includes raw materials, supporting materials, BOP (Factory Overhead Costs), and labor while data collected for consumer preferences includes taste, price, aroma, and packaging. Data analysis using the methods of Hayami, et al., (1987) and Fishbein Multiattribute analysis. The results showed that the added value obtained from rengginang production activities in Kasumewuho Village, Wawotobi District, Konawe Regency amounted to Rp.21,769/kg of raw materials, or about 45 percent of the product value per kg of raw materials. Consumer preferences for the attributes in rengginang products that consumers most consider to make purchases are taste. Keywords: added value; consumen; preferences; rengginang.